2022
DOI: 10.46827/ejmms.v7i4.1317
|View full text |Cite
|
Sign up to set email alerts
|

The Covid-19 Pandemic: The Initiator for Digital Inclusion or Exclusion of Smes in the Bulawayo Metropolitan Province, Zimbabwe

Abstract: <p>The study examined whether the COVID-19 pandemic had created digital opportunities for Small to Medium Entrepreneurs (SMEs) in the Bulawayo Metropolitan Province, Zimbabwe or it had actually exposed their lack of digital acumen. The interpretivist paradigm, a qualitative descriptive approach and a case study design were adopted for this study. The research used semi-structured questionnaires to solicit data from 30 purposively selected small to medium entrepreneurs. Data were thematically analysed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The SMEs do agree unequivocally that technology helps them to stay afloat even in times of the COVID-19 pandemic, which allows them to continue operating their businesses remotely. These results are an indication that SMEs realised that since face-to-face interaction had been banned, they had to come up with alternative, innovative and creative ways of conducting business if they were to remain operational (Nani and Maguraushe, 2022). Thus, the findings concur with Harel (2021) who argued that technologies helped businesses to survive during the pandemic period.…”
Section: Age and Level Of Education Of Smessupporting
confidence: 72%
See 1 more Smart Citation
“…The SMEs do agree unequivocally that technology helps them to stay afloat even in times of the COVID-19 pandemic, which allows them to continue operating their businesses remotely. These results are an indication that SMEs realised that since face-to-face interaction had been banned, they had to come up with alternative, innovative and creative ways of conducting business if they were to remain operational (Nani and Maguraushe, 2022). Thus, the findings concur with Harel (2021) who argued that technologies helped businesses to survive during the pandemic period.…”
Section: Age and Level Of Education Of Smessupporting
confidence: 72%
“…SMEs need to learn digital skills that are relevant to their businesses to reduce digital exclusion (Jere & Ngidi, 2020). In this context, digital exclusion was a result of the failure to adopt digital technologies within businesses, as well as the failure to navigate through and use digital technologies (Nani & Maguraushe, 2022). Harel (2021) suggested that the government can also play a pivotal role in educating SMEs with digital skills as a way of empowering them to survive in times of crises like the COVID-19 pandemic.…”
Section: Background To the Studymentioning
confidence: 99%
“…In the due process, there is a fierce competition among corporates that creates various problems for enhancing creativity (Baer et al , 2010; Nani, 2017). Hence recently, organizations are focusing on positive psychological drives (Younas et al , 2020), positive leadership styles, that is, authentic leadership (Phuong and Takahashi, 2021; Ribeiro et al , 2020), transformational leadership (Kasımoğlu and Ammari, 2020; Shafi et al , 2020), ethical leadership (Chen and Hou, 2016; Javed et al , 2017), servant leadership (Ruiz-Palomino and Zoghbi-Manrique-de-Lara, 2020; van Dierendonck and Rock, 2010; Yoshida et al , 2014) along with perceived organizational support (Akgunduz et al , 2018; Duan et al , 2020), which may promote creativity.…”
Section: Introductionmentioning
confidence: 99%